A review of impact testing on marine composite materials: Part I – Marine impacts on marine composites. (15th March 2018) - Sutherland, L.S.
Abstract: Composite materials are now used throughout the marine industry but their susceptibility to impact events is still an unresolved problem. There is a huge body of work in the area, succinctly summarised here, but the great majority concerns impact events and composite materials more relevant to the aeronautical industry. A discussion of the complexity of the problem in terms of damage and dependence on the many material and impact event parameters shows why there is a need for a review of work specifically considering 'impact on marine composites' due to the distinctive impact events and materials of marine applications. Marine impact scenarios are discussed and comparisons between composite and other construction methods made. Together with parts II and III, this paper gives a comprehensive review of 'marine impact on marine composites', providing a valuable resource for the marine industry and research fields.